NANING PRANOTO IN THE SOUL OF INDONESIA’S LITERATURE - Woro Januarti (fakultas sastra, 2020)
In modern Indonesian literature, it can be said that female writers are still less prestigious than male writers. The problems raised in literature touch a lot with the relationship between men and women, patriarchal culture, and colonialism, accompanied by women's object as a male commodity. Call it a writer in the New Pujangga era like Selasih, then in the independence era Ida Nasutin, Walujati, St. Nuraini, Suwarsih Djojopuspito, to S. Rukiandi. Also N.H. Dini, Hanna Rambe, until in the 2000s, women writers such as Dee Lestari, Ayu Utami, Djenar Maesa Ayu, and others emerged. This research focuses on examining the literary works of Naning Pranoto, who are post-reform and pre-reform writers. The writer Naning Pranoto has produced twenty novels and more than a hundred short stories. Also, to this day, Naning Pranoto is still active in